(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Expansive soils have swelling properties which gives rise to problems in civil engineering. These soils have poor volume stability in the presence of water. Due to their poor geotechnical properties like swelling, shear strength, compressibility, change in moisture content these soil posse’s danger to the projects. In order to build safe structures, these characteristics of black cotton soil need to be modified and improved. However, due to increasing urbanization and based on availability of land for any mega project, it is unavoidable to do construction on expansive soils which are susceptible to damage due to various properties mentioned above. In order to mitigate such damage, it is essential to stabilize such soils using various techniques. Several methods for improving the above-mentioned properties have been investigated in this literature review study.